PELATIHAN AI UNTUK MENDUKUNG KREATIVITAS DAN INOVASI PADA KELOMPOK REMAJA MASJID IKRAAMAN - Edrian Hadinata; Dedy Irwan; Andi Marwan Elhanafi; Ahmad Zakir (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
The rapid development of Artificial Intelligence (AI) has opened new opportunities to support creativity and innovation among young people, including within religious communities. IKRAAMAN mosque youth, as part of the younger generation, possess strategic potential to utilize AI technology productively in da’wah and social activities. This Community Service program aims to enhance AI literacy, technical skills, and creativity of mosque youth through training on the use of AI for creating digital da’wah content. The implementation methods include the introduction of basic AI concepts, hands-on practical training, and mentoring in the development of creative products. Evaluation was conducted by comparing pre-training and post-training scores covering aspects of basic AI literacy, prompting skills, da’wah content creativity, social media product quality, and digital ethics and security. The results show a consistent improvement in participants’ competencies across all assessment aspects, indicating the effectiveness of the training in enhancing skills and fostering an innovative mindset among mosque youth. This program contributes to empowering IKRAAMAN mosque youth to become more adaptive to digital technological developments, more creative in delivering da’wah, and capable of utilizing AI in an ethical and responsible manner